Prevalence of dental anomalies in pediatric patients at Dental and Oral Hospital of Universitas Muhammadiyah Yogyakarta - Laelia Dwi Anggraini; Denna Idryareza Augustyana; Nurrofi Sekarjati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: A dental abnormality is a deviation from the normal shape and structure of the teeth due to interference during growth and development. Various kinds of abnormalities occur, such as anomalies in the size, shape, position, number, and structure of the teeth. These conditions cause problems in the arch length and occlusion of the maxilla and mandible. Purpose: This study aimed to describe the prevalence of developmental dental anomalies in pediatric patients at the Dental and Oral Hospital of Universitas Muhammadiyah Yogyakarta (UMY) and its networks (Qatrunnada Kindergarten, Budi Mulia Dua Taman Siswa Kindergarten, and Muhammadiyah Sapen Pusat Primary School). Methods: A descriptive observational study with a cross-sectional design was conducted. There were 10,714 pediatric patients included. Results: The prevalence of developmental dental anomalies in pediatric patients at Dental and Oral Hospital, UMY and its network was 0.30%. The prevalence of mesiodens, hypodontia, and fusion dental anomalies were 0.14%, 0.056%, and 0.028%, respectively. There was a 0.019% prevalence of microdontia, peg tooth, and amelogenesis imperfecta. The prevalence of taurodontia and gemination was 0.009%. Conclusion: Dental anomalies occurred more frequently in male pediatric patients, and mesiodens was the most prevalent.